(3efXhQ EOGQj cej h ESdGejs - (3gGfj LRGY(B, (3GQJjeIs; (3SGeQ eMeO YchQ(B, s ((3YeGf(B:s (3OGQ GdMGeO(B,s, 2010)
(3eaghe GdNWQ h GOGQJg , CgOGa EOGQI GdNWQ , bjGS GdNWQ h JLejY GdCNWGQ, JLejY GdNWQ h eDSSGJ GdJCejf , JSYjQ h JShjb GdNOeGJ GdJCejfjI , GdbhGYO GdbGfhfjI dYbO GdJCejf , JfXje TQcGJ GdJCejf, Mce GdJCejf aj GdGSdGe h CQGA HYV GdabgGA(B.s
(3eQGLY U(B.235s
Keywords: (3EOGQI (B-(3GdeNGWQs; (3GJNGP GdbQGQGJs; (3GdJCejf (B- (3GdHfhcs